Co3O4 nanotube / g-C3N4 nanosheet composite material and preparation method and application thereof
By preparing Co3O4 nanotube/g-C3N4 nanosheet composite material and using it under the conditions of photothermal activation of H2O2, the problems of low NO removal efficiency and insufficient catalyst stability under low temperature conditions were solved, and efficient NO degradation and catalyst Run stably for a long time.
Patent Information
- Application Number
- CN202211153099.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-09-21
AI Technical Summary
The prior art is difficult to effectively remove NO from industrial flue gas under low temperature conditions, and the catalyst stability and activity are insufficient.
The composite material was prepared by hydrothermal reaction and calcining steps using Co3O4 nanotubes/g-C3N4 nanosheet composite material as the photothermal synergistic catalyst, and the degradation of NO was catalyzed under the conditions of photothermal synergistic activation of H2O2.
The NO removal rate in industrial flue gas has been achieved to reach more than 90%, and the catalyst still maintains good stability and catalytic activity after long-term operation.
Smart Images

Figure CN115920936B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composite material and a preparation method and application thereof, and in particular to a Co3O4 nanotube / g-C3N4 nanosheet composite material and a preparation method thereof and application thereof as a photothermal synergistic catalyst in catalytic degradation of NO in industrial flue gas, belonging to the technical field of photothermal synergistic catalysis. Background Art
[0002] Controlling the emission of nitrogen oxides is one of the main tasks of my country's current atmospheric governance. Photothermal synergistic catalysis combines photocatalysis and thermal catalysis technologies, making up for the shortcomings of photocatalysis and thermal catalysis. It can effectively start and activate the catalyst under low-temperature illumination conditions and produce a synergistic effect to obtain better catalytic activity than photocatalysis and thermal catalysis. It is a promising new catalytic method.
[0003] As a popular material in the field of photocatalysis, graphite carbon nitride (g-C3N4) has the advantages of excellent thermal and chemical stability, narrow band gap that can be excited in the visible spectrum, excellent photoelectric performance and simple manufacturing process. It is an ideal choice for constructing photothermal synergistic catalytic materials. Co3O4 is a p-type semiconductor with a band gap of 1.2-2.1eV. It has high photocatalytic performance and good thermal catalytic performance. The energy band position of Co3O4 and g-C3N4 is suitable for building heterojunctions. The combination of Co3O4 and g-C3N4 can effectively improve the separation efficiency of photogenerated carriers, produce photothermal synergistic effects, and enhance catalytic activity. Drawing on the treatment process of introducing O3, H2O2, PMS, etc. for advanced oxidation in water pollution treatment, H2O2 and other substances can be introduced as a source of free radicals in photothermal synergistic treatment to tap the potential of photothermal synergistic treatment, in order to achieve better treatment effects in the treatment of high-concentration pollutants.
[0004] The application scenario of the photothermal synergistic process is consistent with the application scenario of the low-temperature SCR denitrification process in the current mainstream denitrification process SCR process. Placing the photothermal synergistic process at the tail end of the entire flue gas treatment system has the advantages of easy equipment modification and upgrading and low catalyst poisoning. Compared with the low-temperature SCR process, the photothermal synergistic process has the advantages of being less affected by water vapor and sulfur dioxide in the flue gas and being able to be effectively started in a low-temperature flue gas environment of about 100°C. The Co3O4 / g-C3N4 composite material is used to excite H2O2 under the photothermal synergistic effect to remove high-concentration NO in industrial flue gas, which has research value and significance. Summary of the invention
[0005] The purpose of the present invention is to provide a Co3O4 nanotube / g-C3N4 nanosheet composite material with good catalytic efficiency and stability and capable of catalytically degrading NO in industrial flue gas, as well as a method for preparing the Co3O4 nanotube / g-C3N4 nanosheet composite material using low-cost raw materials and through simple operations.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a Co3O4 nanotube / g-C3N4 nanosheet composite material, characterized in that it comprises the following steps:
[0008] (1) g-C3N4 is prepared by calcining a carbon nitride precursor under a nitrogen or air atmosphere;
[0009] (2) g-C3N4 was further exfoliated into g-C3N4 nanosheets by thermal exfoliation under nitrogen or air atmosphere;
[0010] (3) using g-C3N4 nanosheets, cobalt salt and precipitant as raw materials, using water or a mixture of water and an organic solvent as a reaction solvent, performing a hydrothermal reaction in a hydrothermal reactor after magnetic stirring, and washing and drying the reaction product after the reaction is completed;
[0011] (4) calcining the hydrothermal reaction product under a nitrogen or air atmosphere, and cooling the product after the calcination to obtain a Co3O4 nanotube / g-C3N4 nanosheet composite material.
[0012] Preferably, in step (1), the carbon nitride precursor includes melamine, urea, dicyandiamide and thiourea; the calcination temperature is 500-600° C., and the calcination time is 2-4 hours.
[0013] Preferably, in step (2), the calcination temperature is 450-550° C., and the calcination time is 2-4 hours.
[0014] Preferably, in step (3), the cobalt salt includes cobalt nitrate hexahydrate, cobalt oxalate, cobalt sulfate and cobalt chloride; the precipitant includes urea and ammonium fluoride; the hydrothermal reaction temperature is 60 to 300° C., and the reaction time is 6 to 24 hours.
[0015] Preferably, in step (4), the calcination temperature is 200-350° C., and the calcination time is 1-3 hours.
[0016] A Co3O4 nanotube / g-C3N4 nanosheet composite material, characterized in that it is prepared by any of the methods described above.
[0017] The present invention is beneficial in that:
[0018] (1) The method for preparing the Co3O4 nanotube / g-C3N4 nanosheet composite material provided by the present invention is simple and easy to operate; the raw material cost is low and it is easy to promote and apply;
[0019] (2) The Co3O4 nanotube / g-C3N4 nanosheet composite material prepared by the present invention has an energy band position of Co3O4 and g-C3N4 that is suitable for building a heterojunction. The combination of Co3O4 and g-C3N4 can effectively improve the separation efficiency of photogenerated carriers, so the catalytic activity is higher;
[0020] (3) The Co3O4 nanotube / g-C3N4 nanosheet composite material prepared by the present invention is used to catalyze the degradation of NO in industrial flue gas. Under the conditions of photothermal synergistic activation of H2O2, the NO removal rate can reach a minimum of more than 90% and a maximum of 100%. After long-term operation, the catalytic performance remains very stable and shows good catalytic efficiency and stability under different flue gas environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a SEM image of the Co3O4 nanotube / g-C3N4 nanosheet composite material prepared by the present invention;
[0022] Figure 2 TEM images of the Co3O4 nanotube / g-C3N4 nanosheet composite material prepared by the present invention at different magnifications;
[0023] Figure 3 is a HRTEM image of the Co3O4 nanotube / g-C3N4 nanosheet composite material prepared by the present invention;
[0024] Figure 4 It is the element distribution diagram of the Co3O4 nanotube / g-C3N4 nanosheet composite material prepared by the present invention;
[0025] Figure 5 It is the XRD spectrum of the Co3O4 nanotube / g-C3N4 nanosheet composite material prepared by the present invention;
[0026] Figure 6 This is a graph showing the NO removal rate of the Co3O4 nanotube / g-C3N4 nanosheet composite material prepared by the present invention after continuous operation for 8 hours. DETAILED DESCRIPTION
[0027] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0028] 1. Preparation of Co3O4 nanotube / g-C3N4 nanosheet composites
[0029] Example 1
[0030] In an air atmosphere, 10 g of melamine (carbon nitride precursor) was calcined at 550°C for 3 h to prepare g-C3N4.
[0031] In air atmosphere, g-C3N4 was calcined at 500℃ for 3h by thermal exfoliation method to prepare g-C3N4 nanosheets.
[0032] 0.276 g g-C3N4 nanosheets, 0.2913 g cobalt nitrate hexahydrate (cobalt salt), 0.074 g ammonium fluoride (precipitant) and 0.3 g urea (precipitant) were mixed and dissolved in water, magnetically stirred for 24 h, and then placed in a hydrothermal reactor. The hydrothermal reaction temperature was 120 ° C and the reaction time was 10 h. After the reaction was completed, the reaction product was first washed with distilled water and anhydrous ethanol, and then vacuum freeze-dried.
[0033] The hydrothermal reaction product was calcined at 300°C for 2 h in an air atmosphere. After the calcination, the product was cooled to obtain a Co3O4 nanotube / g-C3N4 nanosheet composite material.
[0034] Example 2
[0035] The difference between this embodiment and embodiment 1 is that the mass of carbon nitride precursor melamine is replaced by urea. The rest is exactly the same as embodiment 1 and will not be described again.
[0036] Example 3
[0037] The difference between this embodiment and embodiment 1 is that during the hydrothermal reaction, the hydrothermal reaction temperature is increased to 140° C. and the reaction time is extended to 12 h. The rest is exactly the same as embodiment 1 and will not be described again.
[0038] Example 4
[0039] The difference between this embodiment and embodiment 1 is that: during the hydrothermal reaction, the amount of g-C3N4 nanosheets added is reduced to 0.092 g (i.e., the proportion of g-C3N4 nanosheets in the Co3O4 nanotube / g-C3N4 nanosheet composite material is reduced). The rest is exactly the same as embodiment 1 and will not be repeated.
[0040] Example 5
[0041] The difference between this embodiment and embodiment 1 is that during the hydrothermal reaction, the hydrothermal reaction temperature is lowered to 100° C. and the reaction time is extended to 12 h. The rest is exactly the same as embodiment 1 and will not be described again.
[0042] 2. Characterization of Co3O4 nanotube / g-C3N4 nanosheet composites
[0043] The SEM image of the Co3O4 nanotube / g-C3N4 nanosheet composite material prepared in Example 1 is shown in Figure 1 , TEM images at different magnifications are shown in Figure 2 , HRTEM image see Figure 3 , element distribution diagram see Figure 4 , XRD spectrum see Figure 5 .
[0044] Depend on Figure 1 It can be seen that Co3O4 presents a typical tubular structure with a diameter of about 100 nm.
[0045] Depend on Figure 2 It can be seen that the Co3O4 nanotubes present a porous structure and a relatively rough surface. The reason for the formation of this structure may be that the fluoride ions in ammonium fluoride are adsorbed on the crystal surface of Co3O4 during the crystallization process, thereby regulating the morphology of Co3O4, and urea is pyrolyzed in the reaction to produce ammonia and nitrogen dioxide gas, which promotes the formation of holes in the nanorods. This structure makes the Co3O4 nanotube / g-C3N4 nanosheet composite material have more active sites and increases the specific surface area.
[0046] Depend on Figure 3 It can be seen that the Co3O4 nanotube / g-C3N4 nanosheet composite material has clear lattice fringes, and the interplanar spacing d values are 0.284nm, 0.244nm and 233nm, corresponding to the (220) crystal plane, (311) crystal plane and (222) crystal plane of Co3O4, respectively.
[0047] Depend on Figure 4 It can be seen that Co, O, C, and N elements exist simultaneously in the Co3O4 nanotube / g-C3N4 nanosheet composite material and are evenly distributed.
[0048] Figures 1 to 4 These results fully demonstrate that Co3O4 nanotubes are successfully loaded on the surface of g-C3N4 nanosheets.
[0049] Depend on Figure 5It can be seen that the XRD spectrum of the Co3O4 nanotube / g-C3N4 nanosheet composite material shows diffraction peaks at 19.1°, 31.4°, 36.8°, 38.7°, 44.8°, 55.4°, 59.4°, 65.3°, 74.1° and 77.3°, corresponding to the (111), (220), (311), (222), (400), (422), (511), (440), (620) and (533) planes of Co3O4, respectively; obvious diffraction peaks appear at 13.1° and 27.4°, corresponding to the characteristic peaks of the (100) plane and (002) plane of the graphite phase carbon nitride structure. The former comes from the stacking of conjugated aromatic rings, and the latter comes from the ordered arrangement of triazine rings.
[0050] The SEM images, TEM images, HRTEM images, element distribution maps and XRD patterns of the Co3O4 nanotube / g-C3N4 nanosheet composite materials prepared in Examples 2 to 5 are basically consistent with the corresponding patterns of the Co3O4 nanotube / g-C3N4 nanosheet composite materials prepared in Example 1.
[0051] 3. Catalytic degradation of NO in industrial flue gas using Co3O4 nanotube / g-C3N4 nanosheet composites
[0052] Weigh 0.1g of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) prepared in each embodiment, ultrasonically disperse it in anhydrous ethanol, and then coat it on 0.2g of quartz wool and place it in a reactor. The NO removal experiment is carried out in a continuous flow reaction device. The flow rate and ratio of NO, N2 and air gas are adjusted by a flow meter. The gas enters the H2O2 atomization device after being fully mixed in the buffer bottle, flows into the reactor together with the atomized H2O2, and is discharged from the outlet of the reaction device after flowing through the catalyst. The temperature of the reactor is controlled by an electric heating jacket, and a 500W xenon lamp is used as the light source.
[0053] NOx removal rate = (NOx concentration at the air inlet - NOx concentration at the air outlet) / NOx concentration at the air inlet * 100%.
[0054] Under the conditions of reaction temperature of 110°C, light, H2O2 concentration of 5%, O2 concentration of 8%, and NO concentration of 300 PPM, after detection and calculation, the NO degradation rate of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) prepared in each embodiment is as follows:
[0055] Table 1 NO degradation rate of different Co3O4 nanotube / g-C3N4 nanosheet composites
[0056] catalyst NO degradation rate Example 1 99% Example 2 97% Example 3 99% Example 4 100% Example 5 92%
[0057] It can be seen from Table 1 that the Co3O4 nanotube / g-C3N4 nanosheet composite materials (catalysts) prepared in each embodiment have good NO degradation effects. The NO degradation rates are 92% in some cases (Example 5), and most of them are basically above 97%, and some can even reach 100% (Example 4).
[0058] Weigh 0.1 g of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) prepared in Example 1, adjust the temperature of the reactor to 80°C and 140°C, respectively, under the conditions of reaction temperature of 80°C / 110°C / 140°C, illumination, H2O2 concentration of 5%, O2 concentration of 8%, and NO concentration of 300 PPM, after detection and calculation, the NO degradation rate of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) prepared in Example 1 is as follows:
[0059] Table 2 NO degradation rate of Co3O4 nanotube / g-C3N4 nanosheet composites at different NO degradation temperatures
[0060]
[0061]
[0062] It can be seen from Table 2 that the NO degradation rate of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) at different NO degradation temperatures is slightly different. The NO degradation rate at a low temperature of 80°C is slightly lower, but still higher than 90%. The optimal NO degradation temperature is 110°C.
[0063] Weigh 0.1g of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) prepared in Example 1, adjust the concentration of H2O2 to 0% and 20% respectively, under the conditions of reaction temperature of 110°C, light, H2O2 concentration of 0% / 5% / 20%, O2 concentration of 8%, and NO concentration of 300PPM, after detection and calculation, the NO degradation rate of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) prepared in Example 1 is as follows:
[0064] Table 3 NO degradation rate of Co3O4 nanotube / g-C3N4 nanosheet composites at different H2O2 concentrations
[0065] catalyst <![CDATA[H2O2 concentration]]> NO degradation rate Example 1 0% 20% Example 1 5% 99% Example 1 20% 98%
[0066] As shown in Table 3, the NO degradation rate of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) is very low when H2O2 is not added, only 20%, and the NO degradation rate is significantly improved when 5-20% H2O2 is added, and is as high as more than 98%. This shows that the photothermal synergistic mechanism of the Co3O4 nanotube / g-C3N4 nanosheet composite material can effectively activate H2O2 to degrade NO.
[0067] Weigh 0.1 g of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) prepared in Example 1, adjust the NO concentration to 600 PPM and 900 PPM respectively, and under the conditions of reaction temperature of 110°C, light, H2O2 concentration of 5%, and O2 concentration of 8%, after detection and calculation, the NO degradation rate of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) prepared in Example 1 is as follows:
[0068] Table 4 NO degradation rate of Co3O4 nanotube / g-C3N4 nanosheet composites at different NO concentrations
[0069] catalyst NO concentration NO degradation rate Example 1 300PPM 99% Example 1 600PPM 96% Example 1 900PPM 91%
[0070] As can be seen from Table 4, the NO degradation rate of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) decreases slightly with the increase of NO concentration, but the lowest NO degradation rate can still reach more than 90%, which is relatively high.
[0071] In order to observe the stability of the catalyst (changes in activity during long-term operation), 0.1 g of the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) prepared in Example 1 was weighed and operated for 8 hours under the conditions of reaction temperature of 110°C, light, NO concentration of 400 PPM, H2O2 concentration of 5%, and O2 concentration of 8%, and the changes in catalytic activity of the catalyst were observed.
[0072] The NO removal rate of the catalyst after continuous operation for 8 hours is shown in the figure Figure 6 .
[0073] from Figure 6 It can be seen that the catalyst started up quickly within 5 minutes and maintained 100% catalytic efficiency in the following 8 hours, which shows that the catalyst has good stability.
[0074] In summary, the Co3O4 nanotube / g-C3N4 nanosheet composite material (catalyst) prepared by the present invention has good catalytic efficiency and stability under different flue gas environments, and the catalytic performance remains very stable after long-term operation.
[0075] It should be noted that the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing a Co3O4 nanotube / g-C3N4 nanosheet composite material, characterized in that: The following steps are involved: (1) g-C3N4 is prepared by calcining a carbon nitride precursor under nitrogen or air atmosphere; (2) g-C3N4 was further exfoliated into g-C3N4 nanosheets by thermal exfoliation in nitrogen or air atmosphere; (3) Using g-C3N4 nanosheets, cobalt nitrate hexahydrate, ammonium fluoride and urea as raw materials, the mass ratio is 0.092g or 0.276g:0.2913g:0.074g:0.3g, using water as the reaction solvent, after magnetic stirring for 24 hours, a hydrothermal reaction is carried out in a hydrothermal reactor, the hydrothermal reaction temperature is 60-300°C, the reaction time is 6-24 hours, and after the reaction is completed, the reaction product is washed and dried; (4) Calcine the hydrothermal reaction product under a nitrogen or air atmosphere, and cool the product after the calcination to obtain a Co3O4 nanotube / g-C3N4 nanosheet composite material.
2. The method according to claim 1, characterized in that: In step (1), the carbon nitride precursor includes melamine, urea, dicyandiamide and thiourea.
3. The method according to claim 1, characterized in that: In step (1), the calcination temperature is 500-600° C. and the calcination time is 2-4 hours.
4. The method according to claim 1, characterized in that: In step (2), the calcination temperature is 450-550° C. and the calcination time is 2-4 hours.
5. The method according to claim 1, characterized in that In step (4), the calcination temperature is 200 to 350° C., and the calcination time is 1 to 3 hours.
Citation Information
Patent Citations
Cobaltosic oxide dodecahedron / carbon nitride nanosheet composite and application thereof in waste gas treatment
CN110180570A